1999
DOI: 10.1128/aem.65.6.2369-2375.1999
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Genotyping of Campylobacter Strains Isolated from Poultry and Humans with Amplified Fragment Length Polymorphism Fingerprinting

Abstract: For epidemiological studies of Campylobacterinfections, molecular typing methods that can differentiate campylobacters at the strain level are needed. In this study we used a recently developed genotyping method, amplified fragment length polymorphism (AFLP), which is based on selective amplification of restriction fragments of chromosomal DNA, for genetic typing ofCampylobacter jejuni and Campylobacter colistrains derived from humans and poultry. We developed an automated AFLP fingerprinting method in which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(88 citation statements)
references
References 29 publications
6
76
1
4
Order By: Relevance
“…These results indicated the method to be as sensitive as macrorestriction pro¢ling with each of four enzymes, and also suggested potential as an identi¢cation tool, since di¡erences in AFLP pro¢les between the two species were evident. Shortly after our study was published, Duim et al [9] showed cluster analysis of HindIII-HhaI-derived AFLP pro¢les delineated C. jejuni subsp. jejuni and C. coli to di¡erent clusters.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…These results indicated the method to be as sensitive as macrorestriction pro¢ling with each of four enzymes, and also suggested potential as an identi¢cation tool, since di¡erences in AFLP pro¢les between the two species were evident. Shortly after our study was published, Duim et al [9] showed cluster analysis of HindIII-HhaI-derived AFLP pro¢les delineated C. jejuni subsp. jejuni and C. coli to di¡erent clusters.…”
Section: Introductionmentioning
confidence: 84%
“…These results may be due to the presence of restriction modi¢cation systems that inhibit the action of one or both of the enzymes used. Such phenomena have been described in Campylobacter species before [6,9,10]. Because of these results, C. helveticus was not considered in any numerical analyses.…”
Section: General Features and Reproducibility Of Aflp Pro¢lesmentioning
confidence: 91%
“…Most (47 of 64) human isolates in this study were in human-only clones. In a Dutch study, including only human and chicken isolates, 3 main clusters were identified, each of which included isolates of both human and chicken origin with no cluster restricted to either host (Duim et al, 1999). In a second Dutch study, including human, chicken and cattle isolates, again no convincing evidence was found for a hostassociation using AFLP .…”
Section: Aflpmentioning
confidence: 98%
“…The consequence is that it is not possible to combine the data from the above PFGE studies for joint analysis. Five AFLP studies have assessed host association and possible sources of human infection but there is little evidence for the capacity of this method to predict source (Duim et al, 1999;.…”
Section: Campylobacter Attribution Using Subtypingmentioning
confidence: 99%
See 1 more Smart Citation